A Boron-10 nitride nanosheet for combinational boron neutron capture therapy and chemotherapy of tumor. (January 2021) - Li, Liping; Dai, Kun; Li, Jiyuan; Shi, Yaxin; Zhang, Zizhu; Liu, Tong; Jun Xie,; Ruiping Zhang,; Liu, Zhibo
Abstract: Combination cancer therapy (e.g., radiochemotherapy) is widely used to enhance the therapeutic effects and prevent the recurrence of cancer. However, the side effects of monotherapy are also amplified when treating cancer with combination therapy. A locally activated drug delivery strategy that can release the payload in a tumor-selective manner is greatly needed to overcome the side effects of combination therapy. Here, we explore the potential of combining boron neutron capture therapy and chemotherapy as a new type of radiochemotherapy. Two-dimensional (2D) boron-10-rich nanosheets (BNNSs) were fabricated as a dual-functional delivery system: targeted boron-10 delivery systems for boron neutron capture therapy (BNCT) and drug delivery vehicles to load doxorubicin for chemotherapy. Irradiated by low-energy thermal neutron, BNNSs can produce high linear energy transfer (LET) particles to kill tumor cells, and the loaded doxorubicin can be released in situ at the same time. This neutron-triggered radiochemotherapy shows noteworthy efficacy in suppressing tumor growth in triple-negative breast cancer. To the best of our knowledge, this is the first report to combine BNCT with chemotherapy as a new type of radiochemotherapy. We hope this study could inspire additional BNCT-induced combination cancer therapies and provide insight for the further clinical translation of BNCT. Graphical abstract: Image 1